Efficacy of Combined Intralesional Triamcilone and Cryotherapy for Treatment of Keloid: Triamcilone and Cryotherapy for Treatment of Keloid - Tahir, Sidra; Tahir, Raheel; Noreen, .; Suleman, Muhammad Talha; Jamil, Muhammad Irfan; Sohaib, Muhammad (Pakistan Journal of Health Sciences, 2025)
Keloid treatment remains a challenging task due to the high recurrence rates and limited effectiveness of monotherapies. Objective: To determine the efficacy of combining intralesional Triamcinolone Acetonide (TA) with cryotherapy. Methods: A quasi-experimental study was conducted at the Dermatology Department, Nishtar Hospital, Multan, over 6 months from 30th June 2024, to December 31, 2024. Eighty patients were enrolled using non-probability consecutive sampling. Baseline characteristics, including keloid dimensions, pain, and itching scores, were documented. Patients received cryotherapy followed by intralesional TA (40 mg/mL) injections for up to six sessions. Treatment outcomes were assessed two weeks post-treatment through reduction in keloid height, length, and Visual Analog Scale (VAS) scores. Results: The mean keloid height and length reduced significantly from 4.66 ± 1.37 mm to 1.69 ± 1.18 mm and 6.64 ± 2.23 cm to 2.68 ± 1.79 cm, respectively (p < 0.001) post-treatment. VAS pain scores decreased by 2.86 ± 1.96, and VAS itching scores decreased by 3.53 ± 1.39 (p < 0.001). Efficacy, defined as ≥50% reduction in keloid dimensions, was achieved in 75% of participants. Common adverse effects included blistering (18.8%) and erythema (15%). Conclusions: The combination of cryotherapy and intralesional triamcinolone acetonide demonstrated effective reduction in keloid height and length, with significant improvement in pain and itching scores. Although efficacy varied across demographic and lesion-specific variables, the treatment remains a safe and viable option for keloid management, with manageable adverse effects and promising outcomes.